2015
DOI: 10.5467/jkess.2015.36.5.484
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of a STEM Integration Teacher Professional Development Program on Secondary Science and Mathematics Teachers' Perceptions of Engineering and Their Attitude toward Engineering Integrated Teaching

Abstract: This study explores the impact of a STEM integration teacher professional development program focusing on teachers' perception of engineering and their attitudes toward integrating engineering into teaching. A total of sixty-eight teachers from ten schools participated in the program for five days. Data are collected from three main sources including (1) pre and post concept maps probing teachers' perceptions about the engineering discipline, (2) a pre and post survey measuring teachers' self-efficacy of teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…Particularly strong themes that arose were those specifically associated with planning and implementing STEM learning activities for K-12 students as a result of the PD. These results are in agreement with the literature which reports that through quality PD, teachers' self-efficacy and dispositions towards STEM positively increase (Nugent et al, 2010;Nadelson et al, 2013;Wang & Nam, 2015). We can connect the quality of the PD back to Vygotsky's constructivism processes and Bandura's social learning theory as participants experienced the authentic STEM instruction through the modeling of the STEM teaching and through social interaction with their peers on the various challenges presented.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Particularly strong themes that arose were those specifically associated with planning and implementing STEM learning activities for K-12 students as a result of the PD. These results are in agreement with the literature which reports that through quality PD, teachers' self-efficacy and dispositions towards STEM positively increase (Nugent et al, 2010;Nadelson et al, 2013;Wang & Nam, 2015). We can connect the quality of the PD back to Vygotsky's constructivism processes and Bandura's social learning theory as participants experienced the authentic STEM instruction through the modeling of the STEM teaching and through social interaction with their peers on the various challenges presented.…”
Section: Discussionsupporting
confidence: 90%
“…Teachers self-efficacy related to STEM teaching, in particular of engineering principles and processes, affect their pedagogical approaches to teaching engineering, thus the importance of this type of PD for teachers (Wang & Nam, 2015). Wang and Nam (2015) revealed that teachers' understanding of engineering and implementation strategies was more concrete with a heightened sense of self-efficacy after engagement in PD.…”
Section: Self-efficacy Of Teachersmentioning
confidence: 99%
See 2 more Smart Citations
“…The engineering piece however is what teachers struggle with the most when implementing STEM into their curriculum (Wang & Nam, 2015). Previously, engineering education was not part of preservice teacher training at any level, however, now that it is part of the NGSS framework, it has become more commonplace, but much work still needs to be done.…”
Section: The "E" In Stemmentioning
confidence: 99%